Should athletes return to activity after cryotherapy? - Pritchard, K. A.; Saliba, S. A. (Journal of Athletic Training, 2014)
Clinical Question: Does local tissue cooling affect immediate functional performance outcomes in a sport situation. Data Sources: Studies were identified by searching MEDLINE, the Cochrane Central Register of Controlled Trials, and EMBASE, each from the earliest available record through April 2011. Combinations of 18 medical subheadings or key words were used to complete the search. Study Selection: This systematic review included only randomized controlled trials and crossover studies published in English that examined human participants who were treated with a local cooling intervention. At least 1 functional performance outcome that was measured before and after a cooling intervention had to be reported. Excluded were studies using whole-body cryotherapy or cold-water immersion above the waist and studies that measured strength or force production during evoked muscle contraction. Data Extraction: Data were extracted by 2 authors using a customized form to evaluate relevant data on study design, eligibility criteria, detailed characteristics of cooling protocols, comparisons, and outcome measures. Disagreement was resolved by consensus or third-party adjudication. To perform an intent-to-treat analysis when possible, data were extracted according to the original allocation groups, and losses to follow-up were noted. The review authors were not blinded to the study author, institution, or journal. For each study, mean differences or standardized mean differences and 95% confidence intervals were calculated for continuous outcomes using RevMan (version 5.1; The Nordic Cochrane Centre, Copenhagen, Denmark). Treatment effects were based on between-groups comparisons (cryotherapy versus control) using postintervention outcomes or within-group comparisons (precryotherapy versus postcryotherapy). If continuous data were missing standard deviations, other statistics including confidence intervals, standard error, t values, P values, or F values were used to calculate the standard deviation. The Cochrane risk-of-bias tool was used to assess the methodologic quality of included studies. Each study was evaluated for sequence generation, allocation concealment, assessor blinding, and incomplete outcome data. Studies were graded as low or high based on the criteria met, but the risk of bias across the studies was consistently high, so meaningful subgroup classifications were not possible. Differences in study quality and intervention details, including duration of cryotherapy interventions and time periods after intervention before follow-up, were potential sources of bias and considered for a subgroup analysis. Main Results: Using the search criteria, the authors originally identified 1449 studies. Of these, after title and abstract review, 99 studies were deemed potentially relevant and kept for further analysis (1350 studies were excluded). Of the 99 potentially relevant studies, 35 were included in the final review (64 studies were excluded), with relevant outcomes of strength, power, vertical jump, endurance, agility, speed, performance accuracy, and dexterity reported. The 64 excluded studies were rejected due to intervention relevancy, outcome relevancy, and non-English language. In the 35 studies meeting the inclusion criteria, 665 healthy participants were assessed. Muscle strength (using an isokinetic dynamometer, cable tensiometer, strain-gauge device, or load cell) was assessed in 25 studies, whole-body exercise (vertical jump height, power, timed hop test, sprint time, and time taken to complete running-based agility tests, including carioca runs, shuttle sprints, T-shuttle, and cocontraction tests) was assessed in 6, performance accuracy (throwing or shooting) was assessed in 2, and hand dexterity was assessed in 2. Outcomes before and immediately after cryotherapy intervention were reported in all studies; additional outcome assessments at times ranging from 5 to 180 minutes postintervention were recorded in 11 studies. The review authors reported a high risk of bias: selection bias (poor randomization and concealment of group allocation), performance and detection bias (poor blinding of assessors), and attrition bias (incomplete data). Because of the diversity of studies, particularly with respect to cryotherapy protocols and the potential for rewarming before the posttest, the effects of cryotherapy on functional performance were mixed. From the included studies, the authors concluded that cryotherapy treatment reduced upper and lower extremity muscle strength immediately after cryotherapy. However, increases in force output after cryotherapy were reported in 5 studies. Regardless of the effect of cryotherapy on strength, the clinical meaningfulness of most of the data may not be important due to variability and small effects. Studies reporting outcomes of muscle endurance resulted in conflicting evidence: endurance increased immediately after cryotherapy in 6, whereas muscle endurance decreased in 3 . These conflicting results limit the ability to draw clinically relevant conclusions about the effect of cryotherapy on muscle endurance. The majority of studies evaluating whole-body exercise demonstrated decreases in performance after cryotherapy; these outcomes included vertical jump, sprint, and agility, even when cryotherapy was applied only to a body part. Additionally, cryotherapy appeared to decrease hand dexterity and throwing accuracy immediately after intervention, although an increase in shooting performance postintervention was reported in 1 study. Conclusions: The authors suggested that the available evidence indicates that athletic performance may be adversely affected when athletes return to play immediately after cryotherapy treatments. Many of the included studies used variable cooling protocols, reflecting differences in time, temperature, and mode of cryotherapy. The majority of the included studies used cryotherapy for at least 20 minutes. However, when considering an immediate return to activity, this cooling duration may not be clinically relevant because cryotherapy applications during practice and competitions usually last less than 20 minutes. When immediate return to activity occurs after cryotherapy, short-duration cold applications or progressive warm-ups should be implemented to prevent a deleterious effect on functional performance.